Pembatalan Sertipikat Hak Milik Atas Tanah Berdasarkan Putusan Verstek Pengadilan Negeri Nomor 34/Pdt.G/2023/Pn.Bgl - Firas Fadhilah; Yamani Yamani; Emelia Kontesa (Jurnal Multidisiplin Dehasen (MUDE), 2026)
A land ownership certificate is an authentic legal document with strong evidentiary value, as stipulated in the Basic Agrarian Law (UUPA) and Government Regulation No. 24 of 1997. However, disputes frequently arise in land administration due to legal defects or administrative errors in the issuance process. This study examines the cancellation of a land ownership certificate based on the Default Judgment (Verstek) of the Bengkulu District Court Decision No. 34/Pdt.G/2023/PN.Bgl, which declared that the issuance of Ownership Certificate No. 06986 over land belonging to Hi. Himin constituted an unlawful act. The research aims to analyze the judge’s legal considerations in issuing the verstek decision and to assess the legal status of the disputed certificate in relation to the authority of the National Land Agency (BPN). The study employs a normative juridical approach by reviewing statutory regulations, legal doctrines, and court decisions. The analysis reveals that the judge rendered the verstek decision based on stronger evidence of ownership presented by the plaintiff, the defendant's absence without legitimate reasons, and indications of administrative defects in the certificate issuance by BPN. Furthermore, a verstek judgment with permanent legal force provides an administrative basis for BPN to cancel the certificate pursuant to Article 29 of Ministerial Regulation ATR/BPN No. 21 of 2020. Thus, a certificate declared legally invalid by a court decision must undergo administrative cancellation through the authorized land office. The findings of this research are expected to contribute to land dispute resolution and strengthen legal certainty within Indonesia’s land administration system.